Facile Preparation of State-of-the Art Thermoelectric Materials by High-pressure Synthesis. (2015) - Serrano, F.; Gharsallah, M.; Cherif, W.; Martínez, J.L.; Cascos, V.; Troncoso, L.; Alonso, J.A.
Abstract: We describe the HP preparation of some state-of the art thermoelectric materials: chalcogenides and pnictides. Those include Bi2 Te3 and materials with skutterudite structure (CoSb3 ). Some present a huge preferred orientation and nanostructuration, resulting from the uniaxial pressure applied during the synthesis, which may be beneficial to enhance the thermoelectric properties. Besides pnictides (group Va) like CoSb3 or AuSb2, we have also prepared semi-metal chalcogenides (group VIa) with NiAs structure (CoTe) or marcasite structure (FeTe2 ). All these materials have been structurally characterized by XRD and NPD (neutrons are useful to prevent preferred orientation problems in the structural resolution) and the three involved magnitudes in the ZT figure of merit have been preliminary characterized in as-grown pellets of the bulk materials.